ผลของสภาวะความเค็มต่อการเปลี่ยนแปลงสมบัติของดินปลูกและการร่วงของใบทุเรียนพันธุ์ก้านยาว - แก้วกมล กันตพงษ์; เชื้อบุญ วิลาวรรณ์; เทพศิลปวิสุทธิ์ อรประภา; อธินุวัฒน์ ดุสิต; เชิดหิรัญกร เบญญา (Thai Journal of Science and Technology, 2019)
Salinity stress affected changing of soil properties and durian tree falling leaves of durian cv. Kan Yao was investigated by watering 90-100 cm height Kan Yao durian with 0.2 (T2), 0.5 (T3), 1.0 (T4), and 2.0 (T5) ppt NaCl solutions every 2 days for 8 weeks compared with control treatment (T1). Soil pH, electrical conductivity (EC), organic matter (OM), available phosphorus (P), exchangeable potassium (K), sodium (Na), Cl (chloride), magnesium (Mg), calcium (Ca), and salt absorption ratio (SAR) and water EC and water salinity were measured by standard methods. The percentage of durian tree falling leaves was observed at week 8 after treated. Results revealed that all concentrations of NaCl solutions (T2-T5) affected soil pH, EC, SAR, Na, and Cl which involving Mg and Ca sediment formed. Salinity stress by watering Kan Yao durian with 1.0 (T4), and 2.0 (T5) ppt NaCl solutions affected durian tree falling leaves within 8 weeks to 79.2 and 100 %, respectively. By the way, watering fresh water in canal with 0.07 ppt salinity also affected durian tree falling leaves within 8 weeks to 53.9 %. Salinity stress did not affect organic matter, P, and K but water EC and water salinity. Therefore, this study indicates that salinity stress affects changes of soil properties and durian tree falling leaves. The water salinity problem needs to be solved immediately for protecting the Kan Yao durian production area in Nontaburi province from salinity stress problem.